THE EFFECT OF COMPANY SIZE, LEVERAGE, AND PROFITABILITY ON TAX AGGRESSIVENESS (Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange for the 2018-2020 Period) - Leriandri Ayuni; Yananto Mihadi Putra (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Tax aggressiveness is an action that has the aim of reducing taxable incomethrough tax planning and using methods that are classified or not classified as tax evasion. This study aims to determine the effect of company size, leverage and profitability on tax aggressiveness. This research is motivated by the importance of information about the factors that affect tax aggressiveness. In 2019, tax evasion occurred in companies with the taxation sector. The population of this study were mining companies listed on the Indonesia Stock Exchange in 2018 - 2020. The sample of this study was 19 issuers or 57 company financial statement data used in this study. This study uses multiple linear regression. The results of this study indicate that leverage has an effect on tax aggressiveness. Meanwhile, firm size and profitability have no effect on tax aggressiveness. This study supports previous research which shows that company size has no effect on tax aggressiveness, leverage has no effect on tax aggressiveness, and profitability has no effect on tax aggressiveness.